A forum that moves mountains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
2002 might be the International Year of the Mountain (see also Spore 97), mountains have been in the spotlight much longer. The Mountain Forum, a global network for anyone working, living or interested in mountain areas, was established in 1995 to...